A global analysis of tandem 3'UTRs in eosinophilic chronic rhinosinusitis with nasal polyps. - Peng Tian (Public Library of Science (PLoS), 2012)
Background Alternative polyadenylation (APA) is emerging as a widespread mechanism of gene regulation. The usage of APA sites allows a single gene to encode multiple mRNA transcripts with different 3'-untranslated region (3'UTR) lengths. Many disease processes reflect the importance of the regulation of APA site switching. The objective of this study was to explore the profiling of tandem APA sites in nasal polyps compared with nasal uncinate process mucosa. Methods Sequencing of APA sites (SAPAS) based on second-generation sequencing technology was undertaken to investigate the use of tandem APA sites and identify gene expression patterns in samples from the nasal polyps and nasal uncinate process mucosa of two patients with chronic rhinosinusitis with nasal polyps. The findings of the SAPAS analysis were validated via quantitative reverse-transcription polymerase chain reaction (qRT-PCR). Results First, the results showed a switching of 3'UTR lengths in nasal polyps compared with nasal uncinate process mucosa. From the two patients, 105 genes that were detected in both patients in the nasal polyps were switched to distal poly(A) sites, and 90 such genes were switched to proximal poly(A) sites. Several Gene Ontology terms were enriched in the list of genes with switched APA sites, including transcription regulation, cell cycle, apoptosis, and metabolism. Second, we detected genes that showed differential expression with at least a 3-fold difference between nasal polyp tissue and nasal uncinate process mucosa. Between the two sample types, 627 genes exhibited differential expression. The qRT-PCR results confirmed our SAPAS results. Conclusion APA site-switching events of 3'UTRs are prevalent in nasal polyp tissue, and the regulation of gene expression mediated by APA may play an important role in the formation and persistence of nasal polyps. Our results may provide new insights into the possible pathophysiologic processes involved in nasal polyps.